Horizontal mergers and product quality - Brekke, Kurt R. (2014)
Using a spatial competition framework with three ex ante identical firms, we study the effects of a horizontal merger on quality, price and welfare. The merging firms always reduce quality. They also increase prices if demand responsiveness to quality is sufficiently low. The non-merging firm, on the other hand, always responds by increasing both quality and prices. Overall, a merger leads to higher average prices and quality in the market. The welfare implications of a merger are not clear-cut. If the demand responsiveness to quality is sufficiently high, some consumers benefit from the merger and social welfare might also increase.